Product Innovation Development in The Creative Industries Aren Handicraft in Jember Regency Tutul Village - Tri Palupi Robustin; Khoirul Ifa; Neny Tri Indianasari; Fetri Setyo Liyundira; Wahyuning Murniati; Ninik Lukiana; Deni Juliasari (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The purpose of this research is how the process of developing product innovation in aren handicraft. Design/methodology/approach: This type of research uses descriptive methods with a qualitative approach. Researchers use the model developed by Urich & Eppinger for the product innovation development process. Findings: The results showed that in phase 5 (Production Ramp Up) workers were able to produce new products from hyacinth raw materials and wood waste with a variety of innovations. Research limitation/implications: The Research is limited to aren handicraft in Village Tutul Jember. Practical implications: This research can be used as a guide for several interested parties, namely lecturers, students and the craft industry Originality/value: This Paper is original Paper Type: Research paper